THE EFFECT OF SAUROPUS ANDROGYNUS LEAVES EXTRACT PLUS TURMERIC POWDER ON FAT DEPOSITION, CARCASS QUALITY AND BLOOD PROFILE IN BROILERS FED LOW PROTEIN DIETS - Santoso, U.; Kususiyah, K.; Suharyanto, S. (Diponegoro University, 2015)
The present study was designed to evaluate the effectiveness of Sauropus androgynus leavesextract (SALE) plus turmeric powder (TP) on carcass quality and blood profile in broilers fed lowprotein diets. Sixty broilers aged 14 days were divided to 5 treatment groups as follows: 1) Broilers fed19% protein diet without SALE plus TP as control (P0); 2) Broilers fed 17% protein diet supplementedto 4.5 g SALE/kg diet plus 0.5% TP (P1); 3) Broilers fed 17% protein diet supplemented to 4.5 gSALE/kg diet plus 1% TP (P2); 4) Broilers fed 15% protein diet supplemented to 4.5 g SALE/kg dietplus 0.5% TP (P3) and; 5) Broilers fed 15% protein diet supplemented to 4.5 g SALE/kg diet plus 1%TP (P4). Supplementation of SALE plus TP significantly affected body weight gain, feed intake, proteinintake, thigh meat haemorrhage and fat deposition (P<0.05). No significantly different was observed oncarcass odor, shank color, breast meat haemorrhage, leg and breast weight, meat cholesterol, fatty liverscore and tocixity (P>0.05). In conclusion suplementation of SALE plus TP had no beneficial effect onreducing fat deposition in broilers fed low protein diets, but it reduced blood uric acid but increasedblood glucose concentration.